The Impact of Nutrition, Physical Activity, Beneficial Microbes, and Fecal Microbiota Transplant for Improving Health - Justine Keathley; Jessica White; Gregor Reid (Life, 2023)
The recognition that microbes are integral to human life has led to studies on how to manipulate them in favor of health outcomes. To date, there has been no conjoint recommendation for the intake of dietary compounds that can complement the ingested organisms in terms of promoting an improved health outcome. The aim of this review is to discuss how beneficial microbes in the form of probiotics, fermented foods, and donor feces are being used to manage health. In addition, we explore the rationale for selecting beneficial microbial strains and aligning diets to accommodate their propagation in the gut. A pilot clinical trial design is presented to examine the effects of probiotics and exercise in patients with phenylketonuria (PKU); it is the most common inborn error of amino acid metabolism, and it is a complication that requires lifelong dietary intervention. The example design is provided to illustrate the importance of using omics technology to see if the intervention elevates neuroactive biogenic amines in the plasma; increases the abundance of Eubacterium rectale, Coprococcus eutactus, Akkermansia muciniphila, or Butyricicoccus; and increases Escherichia/Shigella in the gut, all as markers of improved health. By emphasizing the combined importance of diet, microbial supplements, and the gut microbiome, we hope that future studies will better align these components, not only to improve outcomes, but also to enhance our understanding of the mechanisms.